EpCAM (CD326) Regulates Intestinal Epithelial Integrity and Stem Cells via Rho-Associated Kinase - Takeshi Ouchi; Sohshi Morimura; Lukas E. Dow; Hiroyuki Miyoshi; Mark C. Udey (Cells, 2021)
Humans with biallelic inactivating mutations in Epithelial Cell Adhesion Molecule (EpCAM) develop congenital tufting enteropathy (CTE). To gain mechanistic insights regarding EpCAM function in this disorder, we prepared intestinal epithelial cell (IEC) organoids and spheroids. IEC organoids and spheroids were generated from ROSA-CreERT2 EpCAMfl/fl mice. Proliferation, tight junctions, cell polarity and epithelial integrity were assessed in tamoxifen-induced EpCAM-deficient organoids via confocal immunofluorescence microscopy and Western blotting. Olfm4-expressing stem cells were assessed in IEC cells in vitro and in vivo via fluorescence in situ hybridization. To determine if existing drugs could ameliorate effects of EpCAM deficiency in IEC cells, a variety of pharmacologic inhibitors were screened. Deletion of EpCAM resulted in increased apoptosis and attenuated growth of organoids and spheroids. Selected claudins were destabilized and epithelial integrity was severely compromised. Epithelial integrity was improved by treatment with Rho-associated coiled-coil kinase (ROCK) inhibitors without restoration of claudin expression. Correspondingly, enhanced phosphorylation of myosin light chain, a serine/threonine ROCK substrate, was observed in EpCAM-deficient organoids. Strikingly, frequencies of Olfm4-expressing stem cells in EpCAM-deficient IEC cells in vitro and in vivo were decreased. Treatment with ROCK inhibitors increased numbers of stem cells in EpCAM-deficient organoids and spheroids. Thus, EpCAM regulates intestinal epithelial homeostasis via a signaling pathway that includes ROCK.